Cross species amplification of microsatellite loci from Phytophthora spp to assess genetic diversity among the Phytophthora isolates from black pepper - Babu, M Anandaraj, J Cissin, R S Bhai, K B Vinitha, K N (Journal of Spices and Aromatic Crops, 2016)
Phytophthora capsici is one of the most destructive pathogens of black pepper in India and the world over. Diversity of 114 Phytophthora isolates obtained from leaf, stem, root and soil of different agro climatic areas was studied using 25 SSR primers that were previously described. twenty primers were successfully amplified. Of these, 15 were polymorphic among the Phytophthora isolates and altogether 37 loci were detected. Of the 37 bands generated from 20 primers, 75.67% were polymorphic. Cluster analysis using the unweighted pair-group method with arithmetic averages divided the isolates into seven major groups. The dendrogram generated showed that all the isolates were separated at similarity coefficient between 57-95%. Group 7 with a single isolate stood as an out group. Clustering did not follow the pattern of geographical origin or plant part from where the isolates were obtained.